Genetic variants in taste genes play a role in oral microbial composition and severe early childhood caries - Vivianne Cruz de Jesus; Betty-Anne Mittermuller; Pingzhao Hu; Robert J. Schroth; Prashen Chelikani (iScience, 2022)
Summary: Severe early childhood caries (S-ECC) is a multifactorial disease with strong evidence of genetic inheritance. Previous studies suggest that variants in taste genes are associated with dental caries due to the role of taste proteins in mediating taste preferences, oral innate immunity, and important host-microbial interactions. However, few taste genes have been investigated in caries studies. Therefore, the associations of genetic variants in sweet, bitter, umami, salt, sour, carbonation, and fat taste-related genes with S-ECC and plaque microbial composition (16S and ITS1 rRNA sequencing) were evaluated. The results showed that sixteen variants in seven taste genes (SCNN1D, CA6, TAS2R3, OTOP1, TAS2R5, TAS2R60, and TAS2R4) were associated with S-ECC. Twenty-one variants in twelve taste genes were correlated with relative abundances of bacteria or fungi. These results suggest that S-ECC risk and composition of the plaque microbiome can be partially influenced by genetic variants in genes related to taste sensation.